Comparing push and pull factors affecting migration - Mariusz Urbański (Economies, 2022)
The purpose of this research was to conduct a comparison of the push and pull factors affecting migration between Poland and Romania. The study aimed to find out which among the push and pull factors have a greater effect overall and individually on the migration activities. The study was conducted using primary data collected from migrants in both countries using a structured questionnaire. There were data from 298 and 288 surveys for Poland and Romania, respectively. The push and pull migration framework was applied to guide the study. The model suitability was confirmed satisfactory on validity, reliability and factor analysis. The hypothesis was analyzed and evaluated using multiple regression analysis. The findings of the study indicated that pull factors have a greater influence on migration in these two countries as compared to the push factors. Five out of six (economic, political and social in Poland and economic and political in Romania) pull factors were found significant as compared to two (social in Poland and in Romania) out of six push factors. Pull economic factors were significant determinants of migration in all the countries. Pull political factors were found to have the highest effect in both countries, because they influenced migrants in Romania. Economic factors are the major factors that influence migration, including the hope of finding better jobs and better life in the foreign countries, and these factors should be addressed in the effort to reduce migration. In addition, political issues such as unfair legal system, violent conflicts, underdevelopment, poverty, political instability and corruption should be addressed to control the issue of migration.
Keywords: 330; economic factors; foreign countries; migration; political factors; pull and push factors; social factors